Detection of maple toxins in mare's milk. (18th December 2020) - Sander, Johannes; Terhardt, Michael; Janzen, Nils
Abstract: Background: Plants from the Sapindaceae family that are consumed by horses (maple) and humans (ackee and litchi) are known to contain the toxins hypoglycin A and methylenecyclopropylglycine which cause seasonally occurring myopathy in horses and entero‐encephalopathic sickness in humans. Vertical transmission of these toxins from a mare to her foal has been described once. However the mare's milk was not available for analysis in this case. We investigated mare's milk in a similar case. Objective: We hypothesized that hypoglycin A and methylenecyclopropylglycine, like other amino acids' are secreted into the milk. Animals: Mare with atypical myopathy. Methods: A sample of the mare's milk and 6 commercial horse milk samples were extracted with a methanolic standard solution and analyzed for hypoglycin A, methylenecyclopropylglycine, and metabolites using tandem mass spectrometry after column chromatographic separation. Results: There were hypoglycin A (0.4 μg/L) and the associated metabolites methylenecyclopropylacetyl glycine and carnitine (18.5 and 24.6 μg/L) plus increased concentrations of several acylcarnitines in the milk. The milk also contained methylenecyclopropylformyl glycine and carnitine (0.8 and 60 μg/L). The latter substances were also detected in 1 of 6 commercial horse milk samples. Conclusions and Clinical Importance: Transmission of the maple toxins can occur through mare's milk. Vertical transmission of Sapindacea toxins might also have importance for human medicine, for example, after consumption of ackee or litchi.